Damping Control and Experiment on Active Hydro-Pneumatic Suspension of Sprayer Based on Genetic Algorithm Optimization - Qiao, Chaofan; Wen, Haojun; Liu, Xinyue; Wang, Guangyan (Frontiers in Neurorobotics, 2021)
High ground clearance self-propelled sprayers usually work in complex road conditions. Due to the large body mass, wide spray boom breath and high center of gravity, the body and spray boom swing sharply during work, which affects operation quality and even endangers safety. This paper proposes a control plan for timely-started active hydro-pneumatic suspension, and designs a fuzzy PID control system based on genetic algorithm optimization. First, MATLAB software is used to simulate and analyze the model, so that the fuzzy PID control optimized by genetic algorithm is obtained. When the sprayer drives on D-grade road, as the speed increases, in comparison between the damping effect of the active suspension and traditional passive suspension, the corresponding root mean square value of vehicle body vibration acceleration decreases by 11.36% and 12.36% respectively. On the E-grade road surface, with the increase of speed, the corresponding root mean square value of vehicle body vibration acceleration decreases by 13.25% and 14.89% respectively. Based on indoor bench experiments, the proposed control strategy was verified. Under field road excitation, when the sprayer traveled at 5km/h, the root mean square acceleration values of the passive and active suspensions were 1.080m/s2 and 0.847m/s2, respectively; when the sprayer traveled at 8km/h, the root mean square acceleration values of the passive and active suspensions were 1.412m/s2 and 1.125m/s2 respectively, with the root mean square values of vibration acceleration reduced by 21.57% and 20.33% respectively. Under sand-gravel road condition, when the sprayer traveled at 5km/h, the root mean square acceleration values of the passive and active suspensions were 1.149m/s2 and 0.891m/s2, respectively; when the sprayer traveled at 8km/h, the root-mean-square acceleration values of the passive and active suspensions were 1.572m/s2 and 1.229m/s2, respectively, with the root mean square values of vibration acceleration reduced by 22.45% and 21.82% respectively. During the active control process, the suspension displacement is always kept within the limited range, and as the vehicle speed and road surface level increase, the active suspension has a significantly better damping effect than the passive suspension, which proves effectiveness of the active damping scheme.